An unusual presentation of celiac disease in adult patient. Issue 10 (8th October 2022) - Frioui, Refka; Zaouak, Anissa; Chamli, Amal; Jouini, Raja; Fenniche, Samy; Hammami, Houda
Abstract: Pyoderma gangrenosum is among the exceptional extra‐intestinal manifestations of celiac disease. We report a case of a 52‐year‐old patient who presented with pyoderma gangrenosum that turned out to be the initial presentation of celiac disease. Abstract : We report a case of a 52‐year‐old patient who presented with pyoderma gangrenosum as initial presentation of celiac disease. We highlighted the importance of considering cutaneous manifestations in celiac disease patients presenting in adulthood.